Antral follicular development and oestrous response in oestrous synchronized and naturally cycling goats - Bukar, Muhammad Modu (2011)
At present, most of the information on the pattern of antral follicular development on ruminants were gathered from studies conducted in cattle and sheep. However, very little amount of literature exists for goats, especially the non-seasonal polyoestrous goats domesticated in the humid tropics. Thus, the focus of this thesis was to examine the effects of oestrus synchronisation with PGF2α and P4, alone or in combination, with and without gonadotrophins on antral follicular development in goats. In the first experiment, the effects of oestrus synchronisation with PGF2α and CIDR on follicular development, plasma IGF-1 concentration and its association with follicle population were studied. Twenty-four Boer x Australian feral crossbred goats that were between 3-4 years of age, with a mean bodyweight of 35.0 ± 2.7 kg and a median body condition score of 3 were used in this study. The goats were equally divided into 3 groups: PGF2α (A), CIDR (B) and naturally cycling (C). Group A was synchronised with two intramuscular injections of 125 μg cloprostenol, 11 days apart while Group B was synchronised with CIDR inserted in the vagina for 17 days. Group C was not oestrus synchronised. Three waves of follicular development were most frequently observed (58%), followed by 4 waves (31.6%). There were no significant differences (P>0.05) between treatment groups for the other parameters associated with follicular development. A low positive correlation (r=0.14) was observed between IGF-1 concentration and the number of 3 mm follicles and between IGF-I concentration and mean number of follicles (r=0.13). The low correlation between IGF-1 concentration and follicular population suggests a weak association between plasma IGF-1 concentration and follicular development in goats. The objective of the second experiment was to analyse the effects of PGF2α and P4 methods of oestrus synchronisation with or without eCG and FSH on oestrus response and ovulation rates in the goats. The serum cortisol concentrations were also measured to determine if stress occurred during handling for ultrasonography, in the goats raised under a hot and humid tropical environment. There were 9 groups of goats and each group was synchronised with different protocol using PGF2α, FGA and their combinations and either 5 mg FSH or 300 IU eCG. All the synchronised goats that were given eCG exhibited oestrus (100%). However, the number of follicles was higher (P< 0.05) in FSH synchronised groups than the eCG synchronised groups. It was concluded that the PGF2α + FGA + FSH method of oestrus synchronisation is the most promising alternative to oestrus synchronisation with eCG in goats. The serum cortisol concentrations were not significantly different (P< 0.05) between goats handled for ultrasonography and the control group. The third experiment was conducted to examine the effects of eCG on preovulatory follicle growth and time of ovulation. The number of follicles, maximum size of the ovulatory follicles and time of ovulation in a total of fifty-one FGA + PGF2α + eCG synchronised goats and those without eCG were determined. It was found that eCG significantly (P<0.05) increased the total follicle number, maximum follicle diameter and reduced the time to ovulation by 20 hrs. In conclusion, this is the first report of the pattern of follicular development during natural and synchronised oestrous cycles in non-seasonal polyoestrous goats raised in the hot humid tropics. The effects of oestrus synchronisation with prostaglandin F2α and P4 on follicular development were similar and both hormones increased the number of follicles and IGF-1 concentration in the synchronised and subsequent oestrous cycles compared with the naturally cycling group. Of the FSH-based oestrus synchronisation protocols, the PGF2α + FGA + FSH resulted in higher number of follicles than any of the eCG-based oestrus synchronisation protocols evaluated and is the most promising alternative to oestrus synchronisation with eCG in goats.